The Juridical Basis of Religious Court Judges in Granting Mandatory Will Rights to Non-Muslims: Study of the Analysis of Religious Court Decision Number 263/Pdt.G/2007/PTA.Sby - Agustiar, Agustiar (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2024)
In this study, the main problem is the concept of wills wajibahah which is not yet known in classical fiqh, as well as the lack of provisions in Indonesian legislation that can be used by judges to decide cases of wills wajibahah. As a result, judges in religious courts have struggled to resolve cases of wajibah wills brought before the court. The purpose of this study is to analyze the juridical basis of judges in the Religious Courts in Indonesia in granting the right of compulsory bequest to non-Muslim heirs. The approach used in this research is content analysis. The source of information used is Decision Number 263/Pdt.G/2007/PTA.Sby the decision is then analyzed using the content analysis method. The data used is secondary data consisting of primary legal materials in the form of decisions of Religious Courts in Indonesia regarding mandatory wills, as well as secondary and tertiary legal materials. Data analysis was conducted using qualitative normative analysis method. The findings of this study indicate that the ijtihad of judges in religious courts is based on juridical foundations which include the Law (UU), Compilation of Islamic Law (KHI), verses of the Qur'an, hadith, opinions of scholars, fiqh rules, Maqasid Sharia rules, and qiyas.